Development economics. - Abraham, Akampurira (Diplomica Verlag, 2014)
Development economics entail all the aspects of the development process especially meant for the developing countries to overcome the challenges that impede development. This can be through education, education and man power development, restructuring market incentives, incorporating favorable social and political approaches and practices among other factors. Human beings however need streamlined social and economic systems that are able to achieve development through major changes in social structures, national institutions, cultures and attitudes as well as eradication of poverty, reduction.